(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article is devoted to the organization of the communicative educational environment of preschool institutions by means of architecture and design. The basic requirements and conditions for creating a comfortable environment are considered. Examples of foreign experience in solving problems in this area are given. The necessity of multifaceted approaches to the organization of the environment of children’s institutions is substantiated.